Complexity of care and strategies of self-management in patients with colorectal cancer - Ose, Dominik; Winkler, Eva C.; Berger, Sarah; Baudendistel, Ines; Kamradt, Martina; Eckrich, Felicitas; Szecsenyi, Joachim (Patient preference and adherence, 2017)
Given the inherent complexity of cancer care, in which personal, social, and clinical aspects accumulate and interact over time, self-management support need to become more comprehensive. This study has the following two aims: 1) to analyze and describe the complexity of individual patient situations and 2) to analyze and describe already established self-management strategies of patients to handle this complexity.